Guru Pendidikan Pancasila dan Kewarganegaraan dalam Menanamkan Nilai Anti Korupsi Berbasis Al-Quran - Rochim, Ahmad Abdul; Chirzin, Muhammad (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
Corruption is a deviant act in which a person abuses the trust given to them in a matter or organization for personal gain. This act is considered a serious crime because it can harm the state's finances. This study aims to explore how Civics Education (PKn) teachers integrate anti-corruption values into the teaching and learning process, particularly through a Quran-based approach. It is hoped that the values derived from the verses of the Quran will leave a deeper and more lasting impression on students. This research was conducted at SD Negeri 1 Weru Lor, Cirebon, using a qualitative descriptive method with observation and interview techniques. The results show that Civics teachers have implemented anti-corruption values in their lessons, directly relating them to the teaching material. These values include honesty, responsibility, work ethic, and justice. All the integrated anti-corruption values refer to teachings contained in the Quran.